(3GdhSGFd GdMOjKI ai GdEKHGJ GdLfGFi (B: s (3HUeI GdeN (B- (3HUeI GdMGeV Gdfhhi (BDNA / s - (3GdgGfi eMeO WGjY s; (3eCehf eMeO SdGeI (B: s; (3MSfjf EHQGgje UGdM YHjO (B: s ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI ,s, 2011)
(3bSeJ gPg GdOQGSI Edi HGHjf (B: (3GdChd HUeg GdeN hYQaJ ajI eGgjI HUeI GdeN Ydi CSGS Cf GdeN Ch GdYbd gh eQcR hcGaI GdCYeGd GdJi jbhe HgG GdEfSGf gh GdPi jNWW hjfaP hjSLd GdLQjeI ai PgJg hdcf GdTNU GdHQF dGjhLO dOjg gPG GdeNRhf (B. (3hGdKGfi HUeI GdMGeV Gdfhhi (BDNA(3MjK JHjf Cf dcd TNU HUeg hQGKjI NGUI Hg JejRg Yf ZjQg ef GdfGS hdG JJWGHb EdG ai MGdI GdJhGFe GdeJeGKdI (B. (3hCge GdfJGFL Gf HUeI GdeN JJSe HHYV GdNUGFU hGdeejRGJ hdYd CgegG CfgG JSJNOe ai cTa hEKHGJ CZdH GdLQGFe s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi (B2011s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdGOGQI GdJTQjYjI s; (3HUeI GdMGeV Gdfhhi (BDNA s; (3HUeI GdeN s; (3QSGFd LGeYjIs